Brenda Bowman at Dinner with Judy Chicago: Feminism and Needlework in Carol Shields's A Fairly Conventional Woman - Roy, Wendy (Atlantis, 2008)
Like Judy Chicago's 1979 installation The Dinner Party, Carol Shields's 1982 novel A Fairly Conventional Woman has been criticized as too middle class, too domestic, and not truly feminist. This paper argues, in contrast, that like Chicago's installation, Shields's novel broke ground by exploring gendered aspects of the arts-crafts divide and the role of domestic activities such as quilting as impetuses for social change.